IBM DS8900F architecture and implementation updated for Release 9.3 - Kimmel, Peter; Beukers, Daniel; Cook, Jeff; Feraliev, Bozhidar; Klemm, Jörg; Riggins, Connie; Sabharwal, Gauurav (IBM Redbooks, 2022)
This IBM® Redbooks® publication describes the concepts, architecture, and implementation of the IBM DS8900F family. The book provides reference information to assist readers who need to plan for, install, and configure the DS8900F systems. This edition applies to DS8900F systems with IBM DS8000® Licensed Machine Code (LMC) 7.9.30 (bundle version 89.30.xx.x), referred to as Release 9.3.
Includes bibliographical references
Keywords: Storage area networks (Computer networks); IBM computers; Operating systems (Computers); Computer architecture; Client/server computing; Réseaux de stockage (Informatique); IBM (Ordinateurs); Systèmes d'exploitation (Ordinateurs); Ordinateurs; Architecture; Architecture client-serveur (Informatique); operating systems